Sensor performance evaluation for candidate photon readout systems in the RIPTIDE detector - Pisanti, Claudia; Cecchini, Stefano; Console Camprini, Patrizio; Giacomini, Francesco; Lanzi, Samuele; Massimi, Cristian; Mengarelli, Alberto; Minniti, Triestino; Musumarra, Agatino; Pellegriti, Maria Grazia; Piccioni, Alberto; Ridolfi, Riccardo; et al. (Applied radiation and isotopes, 2025)
This paper describes a comparative study of three optical readout systems for the RIPTIDE detector, focusing on their performance under extreme low luminosity conditions. The systems analysed include the ASI533MM-PRO from ZWO, the ORCA-Quest2 from Hamamatsu, and an MCP-based setup built specifically. A key aspect of this analysis is the method to measure the intensity distribution of the diffraction peaks, produced by a coherent light passing through a single slit to study the photon sensitivity and the noise characteristics of the detectors. A photodiode detector for laser power measurement was used to quantify the total light intensity, which was then correlated with the grey level output recorded by each system. As expected, the results show that the ASI533MM-PRO exhibited lower photon sensitivity and higher background noise than the ORCA-Quest2, which demonstrated the capability of detecting single photons. The MCP setup, despite its higher background noise, benefited from light amplification, enabling detection of lower photon densities. This method of comparison provides a robust framework for evaluating the photon’s detection sensitivity of optical readout systems for high-precision, low-luminosity applications like the RIPTIDE detector. •Different optical detection methods are compared in low-light condition.•A diffraction slit setup was used to evaluate sensitivity and noise performances.•Photon multiplication is necessary for RIPTIDE track imaging applications.